REVAMPING POWER INFRASTRUCTURE: A PATH TO LOWER OPERATIONAL COSTS AND ECONOMIC EMPOWERMENT IN AKWA IBOM STATE - Emmanuel , Okon Bassey; Archibong, Helen Idara (Research Journal of Economics and Sustainable Development, 2024)
Access to reliable electricity is crucial for the success of entrepreneurial businesses. This study explores the impact of power failure on entrepreneurial behavior in Akwa Ibom State, Nigeria, with a focus on Uyo metropolis. Despite previous research on the topic, there is limited research on power failure and entrepreneurial behavior in Akwa Ibom State. Using a descriptive design, the experiences of 120 entrepreneurs across various business sectors were examined. The findings revealed frequent power failures, which affected the daily operation of their businesses, damaging machineries, leading to constant repairs, replacement, loss of patronage and impeding the growth of their businesses. Moreover, power outages hindered the start of the daily operation of entrepreneurial activities. The research highlights the need for policymakers and stakeholders to address the issue of reliable electricity supply to drive business growth and development. Recommendations were provided for the government to take more actions to address power supply challenges to boost businesses and reduce high costs of operation for entrepreneurs.